Metalepsis, grief, and narrative in Aeneid 2 - Lovatt, Helen (Oxford University Press, 2018)
This chapter addresses the question of the emotional functions of metalepsis: does narrative complexity intensify emotional engagement or make it bearable through moments of withdrawal? 6 How does metalepsis contribute to the representation of grief? Is there something metaleptic about intense emotion, especially grief, which can create a numbness or shock that separates the sufferer from a sense of reality? The chapter begins with an examination of narrators and narrating in Aeneid 2. Both Aeneas and Sinon are fascinatingly complex narrators, who use their grief to establish authority and create a positive reception. This complexity encourages constant interplay between narrative levels, which creates dissonances for readers, but ultimately intensifies the emotional response of the various levels of audience. If Dido models Virgil’s ideal response, he was not intending to turn us off. The narrator’s constant presence, in counterfactuals that remind us we are in the pre-determined world of myth, the operation of hindsight which activates lament, and the irony more often associated with tragedy, do not alienate but draw us in. The second section tackles narrative transition: ends of scenes and sequences and changes of setting are often characterized by emotional intensity and lack of narrative realism. Metalepsis often occurs at the edges of narrative, including problematization of the narrator’s knowledge of events, anachronism and focus on the narrator’s physical location. The chapter then examines the epic voice of Aeneas, beginning with similes, which also often feature at the ends of sections both as emotional high points and moments of self-conscious reflection for narrator and narratees. In many ways, Aeneas as narrator takes on the epic voice of the primary narrator, and Aeneas’ narrative as well as that of the primary narrator shows through the other narrative levels.7 When Polites dies ante ora parentum (‘before the face of his fathers’) he is an image of the universality of epic death, and connects to Aeneas’ own desire to die in the storm of book 1. This tendency of epic to speak across time and space as well as audience levels is reinforced by puns and intertextual references, which one would expect to create distance, but which can also serve to enhance immediacy. Most strikingly of all, when Priam is described as a headless body on the shore, the author intrudes with a reference to contemporary Rome and Pompey’s death in the civil wars. This too claims the universality and contemporary relevance of mythic storytelling and seems likely to intensify engagement. Finally, I look briefly at Genette's phrase ‘Virgil “has Dido die”’ and how the death of Dido fits into these ideas about grief and narrative.